Mechanical properties of concrete reinforced with 0.5% bamboo fiber, using the sclerometer and the compression resistance test - Bazán Velarde, Albhert Leonardo; Cruzado Ucañan, José Rodrigo; Carrion Rabanal, Katia Nataly (LACCEI, 2024)
In this research we study the compressive strength, as well as a sclerometry evaluation of concrete reinforced by the addition of 0.5% bamboo fiber. For this, 6 cylindrical specimens were made, classifying them into: pattern concrete and concrete reinforced with 0.5% bamboo fiber. The results obtained in the compression test are, in the pattern concrete an average resistance of 368,922 Kg/cm2 and in the concrete reinforced with 0.5% bamboo fiber an average resistance of 390,830 Kg/cm2; For the sclerometry test, the results were 352.652Kg/cm2 for the pattern concrete and 422.637Kg/cm2 for the fiber-reinforced concrete. These results show a correlation between the presence of bamboo fibers and improvements in both surface hardness and compression resistance, as well as the improvement of physical properties such as preventing cracking. In conclusion, we demonstrate that adding 0.5% bamboo fiber to the concrete mix will increase its compressive strength by 5.6% compared to traditional concrete; Likewise, it will be less workable, but with improvements by avoiding cracking due to contraction.